Green composite Pelepah Pinang, Pati Singkong dan Resin Epoksi Sebagai Material Ramah Lingkungan - Marlinawati, Ni Made; Octavian, I Putu Yudi; Lisdiantari, Ni Luh Gede; Gunawan, I Gede Nengah Wika (Teknik Desain Mekanika, 2021)
Abstractt Composites are made up of two or more different materials. Composites derived from synthetic fibers can cause environmental pollution, so that more environmentally friendly materials are needed, namely cassava starch, betel nut, and epoxy resin. Areca nut has a high cellulose content so it can be used as a filler. Epoksi resin has properties that are difficult to degrade, so cassava starch is used to facilitate the composite degradation process. By using the blend and hand lay up methods, the composite was made in 4 compositions, namely (50:50)%v, (60:40)%v, (75:25)%v, (80:20)%v and respectively The composition was divided into four and added with 0 g, 3 g, 6 g, and 9 g of cassava starch. Based on the tensile test results, the highest modulus of elasticity in sample D9 is 128.84 MPa and the maximum stress in sample A6 is 0.896 N/m2. The impact test that requires the greatest energy is found in samples A6 and D9 with the required energy of 28.1363 Joules. The difference in strength can be caused by the presence of voids. This is also shown by the test results of the surface morphology structure which show that there are still voids in the composite so that the composite strength is not optimal and there are uneven bonds between materials in some samples. Based on thermal testing, it is known that sample A6 has better heat conductivity than other samples with a thermal conductivity value of 0.26 W/mK. The biodegradable test proved that the sample containing a mixture of cassava starch showed a significant change with the average degradation value of the sample after 30 days of burial of 0.018%. Keywords: Composite, Areca Nut, Tensile and Impact Test, Biodegradable Test, Thermal Test, SEM